Charity vs. Revolution: Effective Altruism and the Systemic Change Objection - Syme, Timothy (Ethical theory and moral practice, 2019)
Effective Altruism (EA) encourages affluent people to make significant donations to improve the wellbeing of the world's poor, using quantified and observational methods to identify the most efficient charities. Critics argue that EA is inattentive to the systemic causes of poverty and underestimates the effectiveness of individual contributions to systemic change. EA claims to be open to systemic change but suggests that systemic critiques, such as the socialist critique of capitalism, are unhelpfully vague and serve primarily as hypocritical rationalizations of continued affluence. I reformulate the systemic change objection, rebut the charges of vagueness and bad faith and argue that charity may not be worth doing at all from a purely altruistic perspective. In order to take systemic change seriously, EA must repudiate its narrowly empiricist approach, embrace holistic, interpretive social analysis and make inevitably controversial judgments about the complex dynamics of collective action. These kinds of evidence and judgment cannot be empirically verified but are essential to taking systemic change seriously. EA is thereby forced to sacrifice its a-political approach to altruism. I also highlight the importance of quotidian, extra-political contributions to perpetuating or changing harmful social practices. Radical efforts to resist, subvert and reconstruct harmful social practices, such as those involved in economic decision-making, could be just as effective and demanding as charity. But such efforts may be incompatible with extensive philanthropy, because they can require people to retain some level of affluence for strategic reasons but to repudiate both the acquisition of significant wealth and charity as is currently organized. The wealth and status of some critics of charity may indeed be incompatible with effectively contributing to social change, but the altruistic merits of charity are neither as obvious nor as easily demonstrated as EA believes.